Transformasi Karakter Peserta Didik Akibat Penggunaan Teknologi - Syafitri, Syarifah; Sholeh, Muhammad; Fransiska, Afiona; Tasya, Anas; Amanda, Athylla Friska; Lorenza, Dina Mauliya; Hidayat, Rahmad; Hoiriyah, Verny Nur (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Technology profoundly influences the behavior of today's youth, particularly elementary school students undergoing character development. This study examines technology's impact on student character using a literature review approach, drawing data from journals, academic articles, and relevant literature reviews. Findings highlight technology's dual role in shaping elementary students' character. While it can enhance learning interests, critical skills, and collaboration, excessive use hinders direct social interaction, increases addiction risks, and alters traditional values. Integrating technology with character education necessitates appropriate policies and active involvement from teachers and parents. Balancing cognitive and moral development is crucial in mitigating technology's impact on students. Parents and teachers play pivotal roles in guiding, supervising, and modeling appropriate technology use to foster positive character development and minimize negative effects.